An Analysis of Social Media Discourse on Public Perception of Sustainable Technology - Hafizh, Naufal; Pambayun, Lutfi Nugraha Putra (Proceeding International Conference on Religion, Science and Education, 2025)
In recent decades, sustainable technology has taken center stage in global discourse, underscoring sustainability as a vital issue across multiple facets of human life. This topic encompasses key areas such as environmental preservation and resource management, reflecting the pressing need for innovative strategies that minimize environmental impacts while fostering long-term societal benefits. The study aims to identify recurrent themes, trends, and the interconnections among variables as they manifest within online discourse. Social media, especially Instagram, is utilized as a digital arena where perceptions and opinions regarding sustainability are widely shared and discussed. The initial phase of the study focused on data collection, where public comments on posts specifically related to sustainable technologies were gathered based on predefined criteria. Selected posts centered on technologies aimed at sustainability, capturing public responses that reveal how sustainability and environmental themes are understood and discussed by Generation Z in particular. Leveraging digital tools has significantly enhanced the efficiency of text analysis, allowing for timely and comprehensive data processing. To achieve these analytical goals, this study employs Voyant Tools—a web-based platform designed for text analysis and data visualization. This platform supports various analyses, including word clouds, collocations, and contextual interpretations, which collectively elucidate how topics surrounding sustainability are discussed in public comments. Ultimately, this research posits that public comprehension and perception play an influential role in the successful adoption and integration of sustainable technology in Indonesia. By understanding the ways in which sustainability is perceived, discussed, and supported, stakeholders can develop more effective strategies for promoting sustainable practices and encouraging environmental responsibility within society. This study contributes to the discourse on sustainable technology adoption, offering insights that can guide policymakers, educators, and social influencers in fostering a culture of sustainability among digital users, particularly within the context of Generation Z in Indonesia.